2016
DOI: 10.1007/s40801-016-0065-6
|View full text |Cite
|
Sign up to set email alerts
|

Medicines Management, Medication Errors and Adverse Medication Events in Older People Referred to a Community Nursing Service: A Retrospective Observational Study

Abstract: BackgroundIncreasing numbers of older people are receiving support with medicines management from community nursing services (CNSs) to enable them to live in their own homes. Little is known about these people and the support they receive.ObjectivesTo explore the characteristics of older people referred for medicines management support, type of support provided, medication errors and adverse medication events (AMEs).MethodsA retrospective observational study of a random sample of 100 older people referred to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 32 publications
2
65
0
4
Order By: Relevance
“…Older people receiving medication management support from home nursing services have an average age over 80 years and often have multiple health conditions . They commonly take multiple medicines (average of 10), including medications associated with increased risk of AMEs .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 3 more Smart Citations
“…Older people receiving medication management support from home nursing services have an average age over 80 years and often have multiple health conditions . They commonly take multiple medicines (average of 10), including medications associated with increased risk of AMEs .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Other common factors that predispose home nursing clients to increased risk of AMEs include recent hospital discharge, complex medication regimens, cognitive impairment and poor adherence to medicines . A recent Australian study identified that 41% of home nursing clients experienced medication errors and 13% experienced AMEs requiring hospitalization or medical consultation . Nearly two‐thirds of AMEs were potentially preventable, contributing to avoidable healthcare costs …”
Section: What Is Known and Objectivementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, institutionalized patients had a lower risk of being hospitalized as compared to people cared by their family or proxies, as well as by the community nurse (OR 6.8 and 8.5 vs. 4.3); this association also remained statistically significant in the adjusted analysis. People cared for by CNS are on risk for adverse drug reactions, medication errors, and hospitalization (Eliot et al 2016). Although care by CNS may prevent the need for stationary care (Markle-Reid et al 2006), there might still be an excessive need for it in CNS cared individuals compared to nursing home-dwelling persons.…”
Section: Discussionmentioning
confidence: 99%